Nature on Canvas: Narrations on Human-Nature Relationships through Art-Based Methods in La Paz, Bolivia - Benavides-Frias, Camila (2022)
Arts-based research offers innovative ways to study human-nature relationships. We conducted an exploratory study with inhabitants of the city of La Paz in Bolivia, using drawings as an art-based approach to understand how people value and relate to municipal protected areas. Thirty-seven people participated in a drawing competition organized by one of the municipal protected areas where participants depicted some element (landscape, species) of the protected areas that they considered inspiring and reflective of the importance of these areas. Participants highlighted different protected areas; most drew specific local plants or animals, and they expressed various forms of intrinsic, instrumental and relational values. Our pilot study demonstrates how an arts-based approach has potential as a research tool, revealing underexplored aspects of human-nature relationships. We conclude that arts-based approaches can highlight plural values and local ecological knowledge, which provides opportunities to rethink participatory management and environmental education, and inform policy toward sustainability.